Analysis of Return Effectiveness of People’s Business Credit (KUR) in Gorontalo Province - Lanto Miriatin Amali; Wahid Kurniawan Pulukadang (Journal of International Conference Proceedings (JICP), 2018)
People’s Business Credit, also known as KUR, is currently a product favored by the wider community, especially people who have small and medium businesses, because besides not requiring adequate guarantees, the charging of interest which is still relatively low is another type of credit and the other conditions are not so burdensome for the people who own businesses. However, there are still many customers at this time having a business is reluctant to come to the bank to request KUR credit, especially for farmers, because of ignorance about this government program. This type of credit is a government program but the source of funds is fully owned by the channeling bank and must be returned by the customer who has enjoyed this loan. This study uses secondary data from KUR from 2007 to 2017. By using multiple regregi analysis, it can be seen that the NPL results are 39.7% with an interest rate of 32.9%. Keywords: effectiveness, Return of people’s business credit (KUR)